Sharing Economy: a powerful tool for a new era of sustainability - Cotrim, J. (Research Series - Circular Conversations, 2020)
The so-called “Sharing Economy” (SE) has been gaining more and more relevance in the last few years - especially since 2015, the year that coincides with the inclusion of the term in the Oxford Dictionary. A wide range of stakeholders have increasingly gained a great interest in the SE—namely—in relation with its real nature, reach, scope and implications for the sustainability of the planet and human civilization. Did you know that the Sharing Economy (SE) was nominated as one of the 10 ideas that will change the world, evaluated at $26 billion value in 2013 and, most recently, estimated to have a growth of $335 billion by 2025? In this article, I try to explain—in the most concise way possible—some of the central ideas about the SE, which may contribute to a better clarification of what this new Era of “post-ownership economy” is – with particular incidence on (i) the potential of a partnership between the SE and the United Nations (UN) 2030 Agenda’s Sustainable Development Goals (SDGs) and (ii) the impacts of the SE on the sustainability of the resources of the planet.